MARGIN ANALYSIS AND PROFIT OF CLOVE MARKETING, LEMBO DISTRICT, KONAWE UTARA REGENCY - Leni Saleh (Universitas Kristen Indonesia Toraja, 2022)
This study plans to dissect the advertising edges and benefits of clove promoting which have been completed in Puulemo Town, Lembo Locale, North Konawe Rule. This study was carried out between March and April 2022. Farmers, or 20 percent of the population, were selected at random (simple random sampling). so that a total of 21 farmers participated in the survey. For an example of dealers in clove promoting comprising of 3 gatherers and 2 wholesalers, it was done in a (snowball) way as per data from the ranchers. According to the findings of this study, the following are cloves' marketing channels: Wholesalers, traders, collectors, and farmers At the collector level, the average clove marketing margin was Rp. 15,000/Kg, or Rp, at the wholesaler level. 20,000/Kg. Collectors and wholesalers make an average profit of Rp from distributing the results of their purchases of cloves. 6,758,5000.